THE EFFECT OF LEADERSHIP AND DISCIPLINE TYPE ON EMPLOYEE PERFORMANCE IN STATISTIC CENTER AGENCY KAMPAR REGENCY - Winardo Winardo; Zamhir Basem; Litra Diantara (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to determine the effect of the type of leadership and discipline on employee performance at the Central Bureau of Statistics of Kampar Regency. The population in this study were all employees at the Central Bureau of Statistics of Kampar Regency. The sample of this study used a saturated sampling technique (census), namely 31 employees at the Central Bureau of Statistics, Kampar Regency. The data collection techniques used were questionnaires and research files. The data analysis technique used is multiple linear regression analysis with a significant level (α) of 0.05. The results of this study concluded that the type of leadership and discipline simultaneously had a significant influence on employee performance, with a significant value less than 0.05. The results of the analysis of this study indicate that discipline has a partially significant effect on employee performance at the Central Bureau of Statistics of Kampar Regency. The contribution of the independent variable to the dependent variable is very strong.